Tantangan Globalisasi Teknologi Terhadap Guru di Daerah Terpencil; Sebuah Tinjuan Kritis - Aji, Wahyu; Achruh, A.; R, Rosdiana (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The study aimed to identify the challenges faced by teachers in the 3T area in responding to technological globalization. The globalization of technology has brought about tremendous transformation in the global education system. Versatile and open information dynamics demand serious adaptation of the world of education. However, those advances are not entirely adaptable to teachers serving in the 3T (Leading, Outstanding, and Lagging) area. Through a descriptive qualitative approach with a literature study it was found that infrastructural limitations, low digital literacy, and policy gaps were the main barriers. The study suggests the need for anticipation and solutions undertaken by teachers by gaining maximum support from relevant parties through sustainable and adaptive policy interventions in order to bridge the digital divide between the center and the periphery.